Development of an interactive map for Islay based on WebGIS - Gao, Lu (The University of Edinburgh, 2020)
The emergence of web-based GIS technology has made it possible to integrate, represent and analyse geographical data through the Internet (Dong et al., 2013). Integrating WebGIS technology with a range of data resources, Islay Life Explorer was created for facilitating users to explore historical sites in Islay. The study aims to redevelop the existing ILE system based on academic users’ requirements, focusing on improve its interface and functionality. A user-centered design method was applied through the development of the project to target users and optimize final products. The outcome contains two main achievements, including an upgraded user interface expanding the visible space of the screen and two innovative functionalities – multi-level marker filtering function and family tree function. The marker filtering function allows users to search markers through five main categories and twelve sub categories, along with an extra filtering form for quick querying. The family tree will be generated automatically when users open Family History panel.
The Development of an Interactive Map for Islay based on WebGIS
Keywords: WebGIS; Islay; Historical Research; UCD; Family Tree